Bargaining under Threats: The Effect of Joint Custody Laws on Intimate Partner Violence - Daniel Fernández-Kranz; Natalia Nollenberger; Jennifer Louise Roff (Institute of Labor Economics (IZA), 2020)
We study the effect of a policy change that exogenously shifted bargaining power from mothers to fathers on intimate partner violence. We exploit a quasi-natural experiment based on a series of reforms in Spain that shifted the custody decision from being unilaterally determined by the mother to a joint decision, barring evidence of violence. We find that the policy increased the incidence of joint custody in Spain from less than 11% of all divorces to 40% in just five years. Comparing the evolution of intimate partner violence in treated and control regions and using couples without children as an additional comparison group, we find that the policy led to a large and significant decrease in intimate partner violence, with the largest effects among couples in which the mother was more likely to seek sole custody before the policy change. Consistent with this finding, the policy also led to a significant reduction in female partner homicides in treated regions. Finally, we also find evidence of more police reports by victims of intimate partner violence with a significantly higher proportion of these reports ending in dismissals or non-guilty decisions by the specialized courts. We interpret this finding as evidence of strategic behavior by mothers who want to retain sole custody of their children.
Keywords: D13; J12; J13; I12; K36; 330; intimate partner violence; joint custody; divorce; household bargaining models